Double Side Electromagnetic Interference‐Shielded Bending‐Insensitive Capacitive‐Type Flexible Touch Sensor with Linear Response over a Wide Detection Range. Issue 11 (14th July 2021) - Yoo, Dongwoo; Won, Dong‐Joon; Cho, Woosung; Lim, Jongkyeong; Kim, Joonwon
Abstract: Flexible capacitive‐type touch sensors have significant potential in robotics, foldable displays, and wearable electronics. However, the general parallel‐plate structure of these sensors unintentionally changes initial values and sensitivity in various situations, such as in electromagnetic interference (EMI) and bending. In the present study, a double side EMI‐shielded bending‐insensitive capacitive‐type touch sensor is proposed with a linear response over a wide detection range. The device has a novel design that includes double‐sided silver nanowires (AgNWs) embedded on the surface of pyramidal‐polyurethan sponge (AeSoPS) facing the opposite direction. The double‐sided AeSoPS structure offers various advantages, such as bending‐insensitive property, EMI shielding, and linearity and detection range improvement. The fabricated device exhibits excellent linearity ( R 2 = 0.999) up to 700 kPa, bending‐insensitive property on rigid (up to a radius of curvature of 0.7 mm) and soft surfaces, and accurate pressure measurement with superior EMI shielding effectiveness of 99.9% attenuation from EMI (30 dB within a broad frequency range from 0.5 to 12 GHz). Therefore, the developed sensor with improved performance is promising for use in flexible touch sensors, as it offers reliable sensing functions and EMI protection in various environments. Abstract : Double side electromagentic interference (EMI)‐shielded and bending‐insensitive touch sensor is proposed by implementing a novel structure, composed of a porous dielectric layer with pyramidal‐polyurethan sponge and a conductive layer with silver nanowires embedded on the surface of the structure. This structure contributes toward improving the linear response and pressure detection range and exhibits excellent EMI shielding effectiveness and bending‐insensitive property.